Introduction to public policy and food security - Hendriks, Sheryl L.; Babu, Suresh Chandra (Edward Elgar Publishing, 2024)
With less than a decade to achieve the Sustainable Development Goals (SDGs) by 2030, food insecurity, hunger and malnutrition continue to threaten far too many lives worldwide. Around 2.3 billion people worldwide were moderately or severely food insecure in 2021 (Food and Agricultural Organisation of the United Nations (FAO), et al., 2022). Just under 12 per cent of the global population faced food insecurity at severe levels in 2021, with between 702 and 828 million people affected by hunger (FAO et al., 2022). According to the FAO et al. (2022), the prevalence of undernourishment jumped from 8.0 per cent in 2019 to 9.3 per cent in 2020, but rose more slowly in 2021 to reach 9.8 per cent of the world’s population. Progress towards the SDGs is threatened by ongoing and developing crises and challenges affecting global food availability and distribution as well as a mix of complex economic, political and social access to food.